What remains of recognition? Rereading Fraser and Butler in the algorithmic turn - Rudan, Paola (Scenari, 2023)
Building on Nancy Fraser and Judith Butler’s different uses of the category of recognition in the context of the emergence of identity politics, this essay asks how recognition is reconfigured when the algorithmic has become its dominant social form. The first part will lay out the main lines of their arguments, reconstructing how they articulate the relationship between equality, inequality and difference and between social movements and political institutions. In the second part, Joy Buolamwini’s and Wendy Chun’s critiques of algorithmic technologies will be presented, with the aim of showing that discrimination is a function of algorithmic recognition and that it operates by codifying differences as identities. Finally, Fraser and Butler’s theories of recognition will be reconsidered to test their relevance for a political critique of the algorithm, following the hypothesis that the latter is a social institution whose understanding is increasingly relevant to an effective contestation of neoliberal policies.